Interactions of Aging, Overload, and Creatine Supplementation in Rat Plantaris Muscle - Mark D. Schuenke; Naomi E. Brooks; Robert S. Hikida (Journal of Aging Research)
Attenuation of age-related sarcopenia by creatine supplementation has been equivocal. In this study, plantaris muscles of young (Y; 5m) and aging (A; 24m) Fisher 344 rats underwent four weeks of either control (C), creatine supplementation (Cr), surgical overload (O), or overload plus creatine (OCr). Creatine alone had no effect on muscle fiber cross-sectional area (CSA) or heat shock protein (HSP70) and increased myonuclear domain (MND) only in young rats. Overload increased CSA and HSP70 content in I and IIA fibers, regardless of age, and MND in IIA fibers of YO rats. CSA and MND increased in all fast fibers of YOCr, and CSA increased in I and IIA fibers of AOCr. OCR did not alter HSP70, regardless of age. MND did not change in aging rats, regardless of treatment. These data indicate creatine alone had no significant effect. Creatine with overload produced no additional hypertrophy relative to overload alone and attenuated overload-induced HSP70 expression.